STUDI KUALITATIF TENTANG ANALISIS DISIPLIN KERJA TERHADAP KINERJA PEGAWAI (STUDI KASUS PADA KANTOR INSPEKTORAT PROVINSI PAPUA BARAT DAYA) - Della Matelda Hara; Andi Irwan; Pahmi Pahmi (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the influence of work discipline on employee performance in a government agency. Work discipline is one of the important factors that can increase employee effectiveness and productivity in carrying it out. The research method used is a qualitative approach. Based on the results of the study, it shows that its implementation at the Inspectorate Office of Southwest Papua Province has not been running optimally, especially in aspects of attendance, work procedures, and long hours. The low level of employee attendance is caused by the absence of regulations that strictly regulate work discipline, as well as the lack of implementation of an effective monitoring system such as the use of technology-based attendance. Employee work procedures have also not run according to standards due to the lack of socialization of SOPs and a lack of employee understanding of applicable work procedures, so that the implementation of tasks is not directed. Improving employee performance at the Inspectorate Office of Southwest Papua Province requires comprehensive improvements, especially in aspects of leadership, regulations, HR competencies, and structured and integrated work systems